RANCANG BANGUN ALAT PERAGA ENERGI TEBARUKAN BERBASIS ENERGI SURYA - Ali, Mukhlis; Rendi Effendi (Universitas Nusa Putra, 2022)
Electrical energy is a very important requirement both now and in the future. The electrical energy that we use today still comes from conventional power plant. Conventional power plant will create many threats such as increasing pollution and decreasing fossil fuels. Problems like this will have a bad impact on the future. Utilization of alternative energy is one way to solve these problems. Around us there is a lot of energy that will have the potential for us to develop it into a source of electricity for our daily needs. This energy includes solar energy. The purpose of this research is to create and design a solar powered renewable energy teaching aid. The method used in this process is to collect data, then the design process of the props is carried out. Making props is an important factor in this research so that during the testing process the props do not experience significant obstacles. The design of this power plant aims to make teaching aids as a learning medium and to obtain maximum and more efficient energy quantity results. The props consist of several components, namely solar panels, controllers, inverters, volt ampere meters, batteries (accumulator), cables, lights and mini houses. These props are to show that solar energy can be used to generate electricity that can be used for home lighting purposes.